Phosphorus requirement of Nelore steers - Filho, José Cleto da Silva; Vitti, Dorinha Miriam Silber Schimidt; Neto, Otávio Campos; Abdalla, Adibe Luiz (Pesquisa Agropecuaria Brasileira, 2000)
The nutritional phosphorus (P) requirement of cattle has to consider the minimum endogenous fecal loss of this element. In general, ration formulation is based on foreign tables, without taking Brazilian conditions in consideration. The aim of this study was to determine the endogenous losses of P and to estimate the minimum P requirement of Nelore cattle. Eighteen castrated steers aged 12 months and weighing 190.82±27.53 kg were housed in metabolism cages. In a 30 day experimental period the animals were fed with hay and a concentrate mixture. Different levels of dicalcium phosphate were added to basal diet as to obtain 0.12, 0.24 and 0.36% of P, based on the total dry matter intake. 32P was intravenously injected and endogenous P losses were determined. The minimum endogenous fecal loss for zero P intake calculated by interpolation was 5.72 mg/kg (LW) per day, and for zero balance, the minimum P requirement was 8.84 mg/kg (LW) per day.